The Informational Role of Ownership Networks in Bank Lending - Gao, Haoyu; Ru, Hong; Yang, Xiaoguang (Journal of Financial and Quantitative Analysis, 2022)
Abstract This article documents novel large-sample evidence on the informational role of interfirm ownership networks in bank lending. Using comprehensive loan-level data in China, we find that banks’ internal loan ratings at issuance predict subsequent delinquent events more accurately when borrowers are connected to banks’ existing customers via ownership networks. In post-issuance monitoring for delinquent loans, banks with access to ownership networks manage to downgrade their initial ratings before late payments. These findings suggest that ownership networks facilitate the transmission of private information for bank lending. Moreover, ownership networks are more important for transmitting information related to small and medium enterprises.